Big brother watches you (even when he's dead): Surveillance and long-run conformity - Francesco D'Acunto; Philip Schnorpfeil; Michael Weber (Goethe University, Center for Advanced Studies on the Foundations of Law and Finance (LawFin), 2022)
Lack of privacy due to surveillance of personal data, which is becoming ubiquitous around the world, induces persistent conformity to the norms prevalent under the surveillance regime. We document this channel in a unique laboratory-the widespread surveillance of private citizens in East Germany. Exploiting localized variation in the intensity of surveillance before the fall of the Berlin Wall, we show that, at the present day, individuals who lived in high-surveillance counties are more likely to recall they were spied upon, display more conformist beliefs about society and individual interactions, and are hesitant about institutional and social change. Social conformity is accompanied by conformist economic choices: individuals in high-surveillance counties save more and are less likely to take out credit, consistent with norms of frugality. The lack of differences in risk aversion and binding financial constraints by exposure to surveillance helps to support a beliefs channel.
Keywords: D14; E21; E51; G21; 330; Cultural Finance; History & Finance; Social Learning; Beliefs; Persistence; Household Finance; Behavioral Finance; Big Data; FinTech